Lactic acid, hot water, and microwave treatment to reduce natural microflora and pathogens in vacuum-packaged beef - Kang, D.H.; Crozier-Dodson, B.A.; Jiang, G.; Shi, X.; Fung, Daniel Y. C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Combined lactic acid (2%), hot water, and microwave treatments were used to reduce natural microflora and the pathogens Escherichia coli O157:H7, Salmonella typhimurium, and Listeria monocytogenes in vacuum-packaged beef. Hot water at 158EF followed by vacuum packaging and 5 sec. of microwave were acceptable for microbial reduction. Dipping inoculated meat for 20 sec. into 2% room temperature lactic acid prior to that treatment at 158EF reduced E. coli O157:H7 by 1.05 log CFU/cm2, S. typhimurium by .7 log CFU/cm2, and L. monocytogenes by .85 log CFU/cm2 (CFU is colony forming unit). One log equals a 90% reduction, and 2 log a 99% reduction. With this treatment, meat color reverted to an acceptable value after 14 hr of storage at 39EF. Part 3 of the experiment combined 2% lactic acid and hot water treatments into one step. Dipping for 20 sec. in 176EF, 2% lactic acid then vacuum packaging and microwaving for 5 sec. reduced natural microflora by 1.8 log CFU/cm2, E. coli O157:H7 by 1.18 log CFU/cm2, S. typhimurium by 1.5 log CFU/cm2, and L. monocytogenes by 1.5 log CFU/cm2, with acceptable color values after 14 hr storage at 40EF. This combination was the most effective in reducing both natural and inoculated microorganisms and provides a low-cost alternative for decontamination of meat surfaces.
Keywords: Beef; Pathogens; E. coli O157:H7; S. typhimurium; L. monocytogenes